Le influenze marxiste nell’antropologia pedagogica di Paulo Freire - Valenzano, Nicolò (Studi sulla Formazione/Open Journal of Education, 2021)
Paulo Freire was deeply influenced by Marxist philosophy both as regards some specific aspects of his thought, both for the civil commitment with which he intended to combat capitalist relations of production, and also for the constant search for practices of human emancipation. In this contribution I will focus on the debt to Marx regarding pedagogical anthropology. The centrality of this question lies in the belief that, in Freire, the point of insertion to pedagogical problems is anthropological. In the first section I focus on how Freire met Marx; in the second I deepen some aspect to highlight the link between the two authors; in conclusion I suggest considering Freirian pedagogy as a Marxist way to go beyond Marx.